A Buddhist view of abortion - Lecso, Phillip A. (Journal of religion and health, 1987)
This paper examines the abortion issue from a Buddhist perspective. As the consciousness is held to enter the embryo at conception, it is felt to be fully human at that moment. Thus, Buddhism strongly discourages abortion except in the situation of an immediate threat to the mother's life. Though Buddhism has clearly a "pro-life" position on abortion, the final decision should be left to the pregnant woman.